Oil Price Volatility, Macroeconomic and Islamic Banking Investments: Evidence in Indonesia - Nurfalah, Irfan (Islamic Economics Methodology, 2024)
Oil price volatility refers to fluctuations in oil prices over time due to changes in supply, demand, geopolitical events, market speculation, and other factors. High volatility can have widespread economic implications, particularly for oil-dependent economies and industries. The unpredictable volatility of world crude oil prices has caused the world economy to be in uncertainty and disrupt economic stability. The drastic and rapid movement of world crude oil prices will also affect the macroeconomy and microeconomy in each country. The objectives of the study are: Understand the effect of world crude oil prices, FDI and GDP on Islamic banking investment in Indonesia. The results show that the world crude oil price of Brent oil significantly affects the growth of Islamic Investment Bank in Indonesia. The negative coefficient indicates that an increase in the world price of crude oil brent oil can reduce the growth rate of Islamic Investment Bank in Indonesia.